Evaluation as Pedagogy: Models of Theological and Pastoral Formation - Ligo, Vivian (Catholic Education: A Journal of Inquiry and Practice, 2007)
This essay proposes that there is one process but many points of departure for religious education. Each point of departure requires its own construction to facilitate learning. The constructs presented are Bloom’s taxonomy of learning outcomes in the cognitive domain, Groome’s “shared Christian praxis,” the lectio divina, the Ignatian rules of discernment, and the method in ministry of the Whiteheads. The theory proposed found validation in the task of evaluating written assignments of the candidates to the permanent diaconate of an archdiocese.